2015
DOI: 10.1016/j.atmosenv.2014.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of operational on-line-coupled regional air quality models over Europe and North America in the context of AQMEII phase 2. Part I: Ozone

Abstract: The second phase of the Air Quality Model Evaluation International Initiative (AQMEII) brought together sixteen modeling groups from Europe and North America, running eight operational online-coupled air quality models over Europe and North America on common emissions and boundary conditions. With the advent of online-coupled models providing new capability to quantify the effects of feedback processes, the main aim of this study is to compare the response of coupled air quality models to simulate levels of O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
135
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 159 publications
(161 citation statements)
references
References 64 publications
(5 reference statements)
18
135
2
Order By: Relevance
“…During the second phase of the Air Quality Model Evaluation International Initiative (AQMEII), the majority of the modelling groups using the RMS and CM mechanisms with the WRF-Chem model also reported O 3 concentrations overestimation over the eastern Mediterranean (Im et al, 2015a). However, Mar et al (2016) reported an underestimation of about 5 ppbV on summertime O 3 concentrations WRF-Chem model using the RMS mechanism.…”
Section: Main Gaseous Pollutantsmentioning
confidence: 94%
See 1 more Smart Citation
“…During the second phase of the Air Quality Model Evaluation International Initiative (AQMEII), the majority of the modelling groups using the RMS and CM mechanisms with the WRF-Chem model also reported O 3 concentrations overestimation over the eastern Mediterranean (Im et al, 2015a). However, Mar et al (2016) reported an underestimation of about 5 ppbV on summertime O 3 concentrations WRF-Chem model using the RMS mechanism.…”
Section: Main Gaseous Pollutantsmentioning
confidence: 94%
“…Model performance was strongly influenced from the boundary conditions, especially during autumn and winter. Regarding particulate matter 2.5 µm or less in diameter (PM 2.5 ) concentrations, large overestimations over Europe were reported (Im et al, 2015a). Tuccella et al (2012) compared WRF-Chem model output against ground-based observations over the European domain for the year 2007 with time-invariant boundary conditions.…”
Section: G K Georgiou Et Al: Summer Eastern Mediterranean Air Qualmentioning
confidence: 99%
“…Besides KRV, the Mediterranean KOP and OTL stations, as well as the rural ZAV site, are stations with comparatively high measured nighttime O 3 levels, which results in a low overall bias for all hourly O 3 values for these stations (from −2 to −7 µg m −3 ). Namely, the WRF-Chem model cannot capture well the profound nighttime O 3 reductions (shown also by Žabkar et al, 2013;Im et al, 2015a), which contributes to the overall overprediction of hourly O 3 concentrations (from 10 to 36 µg m −3 ) for stations with very low measured nighttime O 3 concentrations. For sites with the highest positive bias in 1 h O 3 concentrations (TRB, ZAG, HRA and ISK, with bias of 36, 31, 26 and 32 µg m −3 , respectively), this can also be partly explained by the too high altitude of the stations in model orography (Table 1), since the mean O 3 concentration increases with height.…”
Section: Evaluation Of Air Quality Variablesmentioning
confidence: 99%
“…4d) showing slight overprediction of daily PM 10 levels at all stations, which is somewhat surprising due to the fact that nearly all current offline and online coupled chemical transport models show large systematic PM 10 underestimations. For example, within the AQMEII exercise, where 17 modelling groups from Europe and North America were brought together, running eight operational online coupled air quality models over Europe and North America, the rural PM 10 concentrations over Europe were underestimated by all models (model configurations) by up to 66 % while for the urban PM 10 concentrations the underestimations were even much larger (up to 75 %) (Im et al, 2015b). The reason for slight overprediction of PM 10 levels could be to some extent attributed to the high model spatial resolution used in our study.…”
Section: Evaluation Of Air Quality Variablesmentioning
confidence: 99%
“…Because NO 2 mixing ratio is influenced by local effects, such as emission and diffusion, the model overestimation of NO 2 in this study may be caused by the uncertainties in emission inventory and boundary layer conditions. The underestimation of O 3 peaks, particularly on clean days before 14 October, might be because of the model inability to accurately represent the stable boundary layer (Holtslag et al, 2013), the overestimation of titration loss near the source regions (Im et al, 2015), and the model errors in temperature fields (Fig. 2).…”
Section: Chemical Compositionmentioning
confidence: 99%